Understanding Malaysian Malays Communication Characteristics in Reducing Psychological Impact on Flood Victims - Mustaffa, CS; Marzuki, NA; Khalid, MS; Sakdan, MF; Sipon, S (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
Culture has a very important function in the daily lives of Malaysians. In spite of its importance, less attention has been paid to identifying Malaysian ethnic values from their own perspective. Most of previous studies have focused on a universal approach to identify the values of Malaysians. By addressing the gap, this paper hopes to identify a more comprehensive list of values related to Malaysian communication characteristics in flood disaster management context. Over the past decade, flood has become Malaysia's most common natural disaster. Sustainable flood mitigation and relief management is important as it reflects the ruling government for dealing with crisis. The psychological support on victims' wellbeing, during and after the disaster is substantial from the humanitarian perspective. Hence, this paper discusses the communication practices from indigenous perspective to help reduce the psychological impact of flooding. This paper presents qualitative data, based on in-depth interviews with 13 flood victims. The findings indicate that local values are important characteristics of effective communication surplus to the aids that bound to reduce the psychological impact of a disaster. This research intends to contribute in terms of the identification of the local code of conduct in communication in an attempt to obtain insights about flood disaster management. Besides, the outcome of the study could help to develop policies for aid agencies, information resources and community organisations in relation to the competency in communication to advocate the betterment and well-being of flood disaster victims.